Touch, Talk dan Skill Play terhadap Penurunan Kecemasan Anak Pre-School - Padila Padila; Lussyefrida Yanti; Bintang Agustina Pratiwi; Wulan Angraini; Rengga Depri Admaja (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine the comparison of the use of touch and talk Educational Game Tools (APE) and the skill play of playing snakes and ladders to reduce anxiety levels of pre-school age children. This research method is a quantitative study with a quasy experimental design of two groups pretest-posttest design. The results obtained in the Touch and Talk Educational Game Tool (APE) group before the intervention had an average anxiety score of 31.62 and after being given the intervention it was 17.31 with a p-value of 0.000, the group playing snake and ladder had an average The score of anxiety before being given intervention was 31.56 and after being given the intervention it was 24.38 with a p-value of 0.000. The statistical test results obtained p value 0.001 <alpha (0.05). In conclusion, there is a difference between the APE touch and talk group and the snake and ladder playing skill group to reduce the anxiety level of pre-school children. Keywords: Pre School, Skill Play, Touch and Talk